Intestinal microbiota development in the first week of life of preterm newborns - Jessica Santos Passos Costa; Heli Vieira Brandão; Camilla da Cruz Martins; Raquel Guimarães Benevides; Jean Carlos Zambrano Contreras; Luiz Gustavo Sparvoli; Pedro Augusto Ramos Vanzele; Carla Romano Taddei; Tatiana de Oliveira Vieira; Graciete Oliveira Vieira (Jornal de Pediatria)
Objective: This study aimed to evaluate the intestinal microbiota development in the first week of life of preterm newborns (PTNB) treated at a public hospital in a municipality in the Brazilian Northeast. Methods: This is an observational, longitudinal, and descriptive study with 23 PTNBs. Two stool samples were collected from each neonate (fasting/meconium and seventh day of life) for stool microbiota analysis by 16S rRNA gene sequencing. The authors analyzed alpha diversity (Chao1, Shannon, and Simpson indices) and principal coordinates of beta diversity. Results: Forty-six stool samples from 23 PTNBs were analyzed at the taxonomic level. Microbiota's development was dynamic with low diversity. The authors observed a statistical association with the genera Enterobacterales, Streptococcus, Bacteroides, Clostridium_sensu_stricto_1, Enterococcus, and Bifidobacterium in the fasting samples when compared to the day-7 samples. The genus Staphylococcus also dominated at both times. Conclusion: Dynamics were observed in the intestinal microbiota development, with an alpha diversity decrease in the stool samples collected at fasting/meconium and on the seventh day of life.